Protein carbonylation: Proteomics, specificity and relevance to aging. Issue 1 (30th September 2013) - Cabiscol, Elisa; Tamarit, Jordi; Ros, Joaquim; Allan Butterfield, D.; Dalle‐Donne, Isabella
Abstract Detection and quantification of protein carbonyls present in biological samples has become a popular, albeit indirect, method to determine the existence of oxidative stress. Moreover, the rise of proteomics has allowed the identification of the specific proteins targeted by protein carbonylation. This review discusses these methodologies and proteomic strategies and then focuses on the relationship between protein carbonylation and aging and the parameters that may explain the increased sensitivity of certain proteins to protein carbonylation. © 2013 Wiley Periodicals, Inc. Rapid Commun. Mass Spectrom. 33: 21–48, 2014.